Diffusion Mechanism Modeling of Metformin in Human Organic Cationic Amino Acid Transporter one and Functional Impact of S189L, R206C, and G401S Mutation - Cano, Leydy; Soto-Ospina, Alejandro; Araque, Pedronel; Caro-Gomez, Maria Antonieta; Parra-Marin, Maria Victoria; Bedoya, Gabriel; Duque, Constanza (Frontiers in Pharmacology, 2021)
Metformin used as a first-line drug to treat Type 2 Diabetes Mellitus is transported via organic cation channels to soft tissues. Mutations in the SLC22A1 gene, such as Gly401Ser, Ser189Leu, and Arg206Cys, may affect the drug’s therapeutic effect on these patients. This study aims at proposing a potential structural model for drug interactions with the hOCT1 transporter, as well as the impact of these mutations at both topological and electronic structure levels on the channel’s surface, from a chemical point of view with, in addition to exploring the frequency distribution of these mutations in patients from a Colombian population. To chemically understand metformin diffusion, we used an open model from the protein model database, with ID PM0080367, viewed through UCSF Chimera. The effect of the mutations was assessed using computational hybrid Quantum Mechanics/Molecular Mechanics, based on the Austin Model 1 semi-empirical method using Spartan 18' software, whereas mutations were genotyped using KASP-PCR in a sample of 393 patients. The results demonstrate coupling energy for metformin with Phe, Trp, His, and Tyr, because of the interaction between the metformin dication and the electron cloud of π orbitals. The mutations analyzed showed changes in the chemical polarity and topology of the structure. For the ancestral allele, the he frequency distribution for this study population was monomorphic. The proposed diffusion model is a possible approach to the interaction mechanism between metformin and its transporter, as well as the impacts of variants, suggesting structural changes in the action of the drug, although no mutations were identified for this study population.